The Importance Of Needs Analysis In Materials Development - Azis Hariyadi, Desi Rizma Yanti (Jurnal Ilmiah Profesi Pendidikan, 2019)
Abstract : There is an issue which can be the subject of a further research that is: most learners of EFL do not actually have any needs at all. They are learning English because they have to rather than because they want or need to. This is particularly true of young learners, who are not going to need to communicate in English for many years to come (if at all). In such cases, the teacher is unlikely to be able to create much intrinsic motivation to learn English in general but can create the need in an engaging classroom task in which the students need to find a way of communicating in English in order to successfully complete the task. This can lead to readiness for acquisition provided the students are motivated by the teacher to read extensively as well. Thus, there should be more place for needs analysis because when we do not run the first principle to create and produce better materials, the rest will always be under great doubt. Every new teacher should consider starting their year applying needs analysis in small scales and then decide what the best is for themselves and their learners.Keywords : Needs analysis, material development